Learning strategies. Definitions, classifications and measuring instruments - Meza, Aníbal (2013)
Definition of learning as a constructive activity is given and classifications of learning strategies are revised, discussing aditionaly their value as resources for improving learning. Main caracteristcs of three instruments for assessing learning strategies are outlined.